Diel niche variation in mammals associated with expanded trait space - D. T. C. Cox (Nature Portfolio, 2021)
Most mammals are nocturnal, but a new analysis suggests that although most groups of species active at a particular time of day or night occupy different ecological niches, a surprisingly large proportion of species are more flexible in the timing of their activity than previously thought.